Hubungan Manajemen Waktu dan Dukungan Sosial Teman Sebaya Dengan Prokrastinasi Akademik Pada Siswa Kelas XII SMAN 4 Bekasi - Rahma Mediastuti; Rr Dini Diah Nurhadianti (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The purpose of this study was to see the relationship between time management andpeer social support with academic procrastination of student of class XII in SMAN4 Bekasi. The subjects of this study was the student of class XII in SMAN 4 Bekasi,with a population of 358 students. The sampling technique used is the conveniencesampling. This research is a quantitative study that uses 3 measuring instruments,namely: academic procrastination scale, time management scale, and peer socialsupport scale. The results showed that there was a significant and negativerelationship between time management and academic procrastination with r -0.762and p = 0.000 < 0.05. There was a significant and negative relationship betweenpeer social support and academic procrastination with r -0.354 and p = 0.000 <0.05. There was a significant relationship between time management and peersocial support with academic procrastination of student of class XII in SMAN 4Bekasi with R = 0.767 and p = 0.000 < 0.05.